Fundamental of Entrepreneurship ENT300 : UniFilem Photography / Audelia Nelly Anak Tommy... [et al.] - Tommy, Audelia Nelly; Mohd Sabirin, Nur Hafiza; Timothy Balai, Tania Mandut; Bujak, Florance Sharanie (2015)
In business, administration planning is the most important aspect in an organization. Through administration planning, all strategies and problem that affect business can be recognised easily before the business can be run, With the well-organized systems, we can prepare the structure on how to run the busmess effectively to make sure that we want to run is successful and have potential to compete with the other competitors 111 business world. The administration will manage the business using the process of Planning, Leading, Organizing and Controlling so that the business will be more effective, efficient and easy to manage.